PENGARUH CORPORATE GOVERNANCE DAN KOMPENSASI EKSEKUTIF TERHADAP AGRESIVITAS PAJAK - Yuwono Yuwono; Fuad Fuad (Diponegoro Journal of Accounting, 2019)
This research purpose is to analyze the effect of executive compensation and corporate governance (the amount of board directors, proportion of independent commissioner, diversification of gender, the age of president director, and the term of president director) on tax aggressiveness, using control variable such as size, return on asset (ROA) and capital intensity (CINT). Tax aggressiveness is measured by effective tax rate (ETR). This research uses quantitative method by using multiple linear regression analysis. The population in this research is all financial sectors firm listed in the Indonesia Stock Exchange from 2014 - 2016. The sample is selected using purposive sampling method and acquired 176 firms.The result showed that the size of the amount of board director, proportion of independent commissioner, executive compensation, and the age of president director effect significantly on tax aggressiveness. Meanwhile, the term of president director and diversification of gender does not significantly influence on tax aggressiveness